EMPLOYEES` PARTICIPATION AND PERFORMANCE IN SMALL AND MEDIUM-SCALE ICT ENTERPRISES OF OBIO/AKPOR LOCAL GOVERNMENT AREA OF RIVERS STATE (NAU Journal of Technology and Vocational Education, 2025)
Employees` involvement in business process seem to have proven positive performance. Therefore, this study determined Employees` Participation and Performance in Small and Medium-Scale ICT Enterprises of Obio/Akpor Local Government Area of Rivers State. Three research questions guided the study and three null hypotheses were tested. Correlational research design was adopted. From a population of 162 SMS ICT Enterprises, a census survey sampling was employed.  A four-point response options questionnaire was used for data collection, and it was validated by three experts. The reliability of the instrument was established using Cronbach’s alpha which yielded coefficients of 0.73, 0.74.and 0.76. Mean and Standard Deviation were used to answer the three research questions and measure the spread in respondents` opinions, while PPMC was used to test the three null hypotheses at 0.05 level of significance. Findings revealed a very high positive relationship between co-ownership and market share, delegation of authority and sales growth, and high positive relationship between employees’ consultation and customers retention. It was concluded that if SMS ICT Enterprises adopt co-ownership, delegation of authority and employees’ consultation in management of their businesses, it will lead to a very high Performances. Among other things, it was recommended that SMS ICT enterprises should adopt co-ownership in the management of their businesses.
Keywords: Small and Medium-Scale (SMS); SMS ICT Enterprises; Performance of Small and Medium-Scale ICT Enterprises; Employee Participation